The Mechanism of Mitral Regurgitation Influences the Temporal Dynamics of the Vena Contracta Area as Measured with Color Flow Doppler. (February 2016) - Cobey, Frederick C.; Ashihkmina, Elena; Edrich, Thomas; Fox, John; Shook, Douglas; Bollen, Bruce; Breeze, Janis L.; Sanouri Ursprung, Wannakuwatte Waduge; Shernan, Stanton K.
Abstract : BACKGROUND: In patients with mitral regurgitation (MR), the effective regurgitant orifice area can be estimated by measuring the vena contracta area (VCA). We hypothesize that the VCA has characteristic temporal dynamics related to the underlying mechanism of functional mitral regurgitation (FMR) versus degenerative mitral valve disease (DMVD). METHODS: VCA measurements obtained by planimetry of the proximal jet from 3D transesophageal echocardiographic (TEE) color flow Doppler data sets were acquired in 42 cardiac surgical patients, including 22 with FMR and 20 with DMVD. Serial VCAs were measured throughout systole for each patient to evaluate variation in the effective regurgitant orifice area. Tercile averages were compared within and between the FMR and DMVD groups using repeated measures analysis of variance. Pairwise tests were Bonferroni-corrected for the number of comparisons. RESULTS: Normalized average VCA values in patients with FMR revealed a biphasic pattern compared with a monophasic pattern in patients with DMVD. Among FMR patients, normalized average VCA values in early (1.10 ± 0.32 cm 2 ) and late systole (1.11 ± 0.33 cm 2 ) were similar but were both significantly greater compared with mid-systole (0.79 ± 0.22 cm 2 ; P = 0.0144 and P = 0.0106, respectively). Among DMVD patients, normalized average VCA values in mid-systole (1.37 ± 0.15 cm 2 ) were significantly greater than those in early (0.53 ± 0.14 cm 2 ) and late systole (1.09 ± 0.18 cm 2 ; P < 0.0001 for both). An analysis of normalized average VCAs also revealed significant differences between the FMR and the DMVD groups during early (1.10 ± 0.32 cm 2 vs 0.53 ± 0.14 cm 2 ) and mid-systole (0.79 ± 0.22 cm 2 vs 1.37 ± 0.15 cm 2 ; P < 0.0001 for both). CONCLUSIONS: VCA dynamics are governed by the mechanism of MR and are observed in FMR patients primarily as a biphasic temporal pattern compared with a monophasic temporal pattern in patients with DMVD. Abstract : Published ahead of print November 9, 2015